Urban heat island research at high latitudes — utilising Finland as an example - Drebs Achim; Suomi Juuso; Mäkelä Antti (Finnish Environment Institute, 2025)
The effects of a built environment on its climate, i.e., the urban heat island (UHI), has been under extensive research for more than 200 years. However, most of the research has focused on cities and regions at low and mid-level latitudes, while cities positioned at high latitudes have gained much less interest. In this article, we focus on summarising a total of 22 Finnish UHI research studies from 1961 to 2021 in cities located between the 60° and 65° north latitude. In these research studies, statements are made about UHI intensity and extent, and about the utilised analysis methods and techniques. Nine of the studies refer to the Finnish capital Helsinki, while the others concern the larger cities Turku, Oulu, and Lahti, as well as the medium-sized municipalities Hyvinkää and Joensuu. Our paper presents the previous studies in chronological order, thereby illustrating the methodological development of UHI research in Finland. One of the most important findings is that the past Finnish studies show a high level of scientific understanding and similar scientific practices to those in corresponding international research. However, the study also shows the challenges of comparing UHI characteristics between different cities because the specific local features (such as topography, water proximity, green infrastructure, etc.) typically play a significant role in local climatological conditions. The results of our investigation show that, firstly, there is a significant difference between the intensity of the summer and winter urban heat island. The UHI intensity can reach up to 14 K under the influence of local conditions. Secondly, the urban heat island intensity, where it could be studied over a longer period of time, has not essentially increased. However, there have been initial indications of an increase in recent studies. Thirdly, the research methods and results show a consistency in content over time, so that early research results can serve as the basis of further investigations. This study highlights the challenging nature of observing urban climate in high spatial-temporal detail and the different methods that have been traditionally used for UHI examinations: the conclusions are that all of these methods are also needed at present in order to grasp the full picture of urban climatic characteristics.